Nanocoral Ag for nonenzymatic glucose detection at extremely low operational potential. (June 2021) - Hill-Dick, Johvan O.; Harmon, Alexis; Cao, Wei; Sadasivuni, Kishor K.; Elahi, Mehran; Adedeji, Adetayo; Elsayed-Ali, Hani E.; Slaughter, Gymama; Kumar, Kapil; Asadi, Mohammad; Kumar, Bijandra
Abstract: Silver (Ag) metal has excellent antibacterial properties, which makes it an ideal candidate for nonenzymatic glucose sensing devices. However, Ag nonenzymatic glucose sensors function at significantly high operating potential and suffer from poor selectivity. Here, we report that nanocoral reduced Ag (R-Ag) based nonenzymatic glucose sensors can be operated at potential as low as 0.1 V vs. Ag/AgCl and exhibits more than one order magnitude higher sensitivity in comparison to the Ag film. The R-Ag sensors can detect glucose in a wide range of concentrations varying from 100 u M to 2.5 mM linearly. The R-Ag sensors are also very robust, as performance remains unchanged even if sensors are stored under ambient conditions for 45 days.